Assessment of general and professional competences formation level by bachelors studying of specialty 101 Ecology - N. V. Maksymenko (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія, 2022)
Purpose. To identify the gaps and weak points of the Education-and-professional programme for the Specialty 101 Ecology based on students' self-assessment of the formation of competencies to improve the training of bachelor's degree specialists.